Pemanfaatan Ekowisata Mangrove sebagai Sumber Belajar IPA bagi peserta didik SMP - Annisa Setiawan; Suyanta Suyanta; Asri Widowati (Postgraduate, University of Mataram, 2024)
The research was carried out with the aim of finding out the use of mangrove ecotourism as a learning resource, because almost all regions in Indonesia manage mangrove ecosystem areas into ecotourism. The data collection technique uses proportional random sampling, with descriptive quantitative research methods. The research subjects used in this research process were the population of junior high school students and junior high school science teachers, with a sample of 118 students and 22 science teachers. The instrument used in this research is a questionnaire. The results obtained from the science teacher questionnaire stated that 80.8% of teachers had never integrated mangroves in the science learning process, reinforced by the results of the student questionnaire which stated that 83.2% of teachers had never presented mangrove material in the classroom. In this way, science teachers should change the way they deliver material using the Argument Driven Inquiry (ADI) learning model to make it easier for science teachers to utilize mangrove ecotourism as a learning resource through the stages of the learning model syntax.